Beliefs about sources of knowledge predict motivation for learning in teacher education. (August 2015) - Bråten, Ivar; Ferguson, Leila E.
Abstract: The purpose of this study was to provide new understanding concerning the theory-practice gap in teacher education. Participants, who were 96 Norwegian student teachers, were found to believe more in practically-derived than in theory-based sources of knowledge about instruction and student learning and to be more motivated for learning from practice than from theory in teacher education. Moreover, stronger beliefs in theory-based sources of knowledge were related to higher motivation to learn from theoretically-oriented coursework and stronger beliefs in practically-derived sources were related to higher motivation to learn from teaching practice. Theoretical and educational implications of the findings are discussed. Highlights: Beliefs about sources of knowledge and motivation to learn were assessed. Beliefs in experiential sources were stronger than in formalized sources. Motivation to learn from practice was higher than motivation to learn from theory. Beliefs in experiential sources predicted motivation to learn from practice. Beliefs in formalized sources predicted motivation to learn from theory.